Family and school: a study from social representations of Basic Education students (Olhar de Professor, 2024)
This paper highlights social representations of students in the final years of elementary school regarding the family and school relationship. Theoretical framework focuses on dimensional and structural approach to the social representations theory. Data were collected by applying a questionnaire to 407 students from 6th to 9th grade in two state schools located on the outskirts of Ponta Grossa - PR city. The analysis of closed questions was based on frequency and percentage; open questions were based on the assumptions of content analysis, with help of EVOC software. Findings indicated presence of ambivalence in the students’ social representations. On one side, there are elements that represent positive attitudes, such as important, respect, helping and education, and on the other, there are elements showing negative feelings, such as anxiety, anger and sadness. This ambivalence highlights presence of silent zone in social representation of family and school relationship.
Keywords: Students; Conceptions; Family-School